Janus amphiphilic nanofiber membranes synergistically drive antibacterial and anti-inflammatory strategies for skin wound healing. (March 2023) - Shi, Yupeng; Zhou, Mengyang; Zhao, Shuo; Li, Haotian; Wang, Wenhao; Cheng, Jingliang; Jin, Lin; Wang, Yifei
Graphical abstract: Highlights: The drug-loaded amphiphilic nanofiber membrane is prepared by electrospinning technology. Gradient release of hydrophilic and hydrophobic drugs under multiple stimulation. Cooperate with antibacterial and anti-inflammatory functions to achieve effective wound healing. The nanofiber membrane shows low biological toxicity and good biocompatibility. Abstract: Prevention of bacterial infection and control of inflammatory responses play critical roles in wound healing. Wound dressing loaded with antibacterial or anti-inflammatory drugs/molecules is one of the feasible routes in clinical applications. Nonetheless, effective and controllable drug release remains challenging. Herein, by electrospinning polyvinyl alcohol (PVA), polylactic acid-glycolic acid (PLGA) with copper sulfide nanoparticles (CuS NPs) and two model drugs, namely antibacterial drugs (mupirocin, M) and anti-inflammatory drugs (valsartan, V), an operable wound-healing patch consist of amphiphilic Janus nanofiber membrane (PLGAV-CuS/PVAM) was prepared which was used to controllable gradient drug release in wound healing. Janus nanofiber membrane shows typical amphiphilic characteristics, with low biological toxicity and good biocompatibility. In vitro experiments showed that the nanofiber membrane could slowly and continuously release mupirocin in a hydrophilic environment for antibacterial purposes. In addition, the excellent photothermal effect of PLGAV CuS/PVAM can regulate the release rate of the anti-inflammatory drug valsartan, effectively reduce the inflammatory reaction in the wound healing process, and also show enhanced bacteriostasis efficiency (96.3% of Escherichia coli and 97.8% of Staphylococcus aureus). The prepared patches exhibited excellent antibacterial, anti-inflammatory, and sustained-release effects, which is of great significance for board the avenue of nanofiber in the biomedical field.